Analisis Pengendalian Kualitas Part 3060HD pada Industri Sparepart Otomotif Menggunakan Metode Statistical Quality Control - Elaeys Mulia Bulqis; Dede Roni (Fakultas Teknik Universitas Tulang Bawang, 2026)
Quality is a characteristic or value inherent in a product and plays an important role in maintaining a company’s competitiveness. An automotive spare parts company producing tool holders, with part 3060HD as its flagship product, experienced quality problems in the form of fluctuating and unstable defect levels during the period from January to October 2024. This condition potentially causes financial losses because the defect rate has exceeded the tolerance limit set by the company. Therefore, this study aims to determine the level of defects that occur, analyze the factors causing defects at each stage of the production process, and formulate improvement efforts to reduce the number of defective products. The method used in this study is Statistical Quality Control (SQC). Based on production data from January to October 2024 with a total production of 3,623,736 units, the number of defective products for part 3060HD was 47,572 units, consisting of 27 types of defects and 1 mixed defect type. The highest defect was caused by synchronization tool change problems, with a total of 6,365 defective units. The analysis results indicate that defects are influenced by man, method, machine, material, measurement, and environment factors. The results of this study are expected to serve as a reference for the company in implementing continuous improvement to enhance product quality and minimize defect rates. Keywords: Defect, Quality Control, Repair, Statistical Quality Control